Geneology Of Sufism: Meaning, Origin and It’s Impact to Java’s Sufi Movements - Hamid, Idrus Al (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this article to discuss two fundamental issues, namely: How Islamic Sufistic Geneology in historical tracking and how the influence of Sufistic thoughts and teachings of Imam Jakfar Sadiq in the dissemination of Islam in the land of Java. The data was collected through reading and studying texts as well as tracing the history which was further analyzed descriptively with the Content analysis method. The results of the study concluded that; Sufistic Islamic Geneology in historical tracking, especially in the land of Java, leads to Imam Ja’far Sadiq. This can be seen from the ancestry (nasab) of the nine saints (Walisongo) Geneology, the famous Islamic preacher on the Java land. It can be traced to the Prophet Muhammad, as quoted from the book of Al-Islam fi Banten. In this context, not many studies explored in detail the construction of Sufism teachings from Walisongo which is an actualization of the concept of Al-Alawiyyah Tariqat reflected in the attitudes, behaviors, and methods of preaching. Suggestions for further research are that in conducting studies and research on the historicity of the propagation of Islam in the Indonesia archipelago (Nusantara), especially on the Java island. It should be conducted comprehensively so that it is not trapped by group fanaticism. The adherents understand that Sunni and Alawiyyun teachings are a chain link between one another. No demarcation line should be drawn that separates the two as if the Ahlul Bait is not Sunni. Thus, conflict of the difference in understanding between Sunni and Ahlul Bait need not occur.